Es procíclica la convergencia del crecimiento económico de américa latina? - María Isabel Osorio Caballero (Investigación Económica, 2019)
– This paper looks at the hypothesis of conditional convergence of Gross Domestic Product (GDP) per capita for a set of eighteen Latin American countries establishing a positive link with the growth rate of those economies. To that purpose, Ø-convergence, σ-convergence and Ú-convergence analyses are conducted. Furthermore, with the aim of identifying spatial heterogeneity the relationship among neighbor territorial units and product levels are studied applying the I Moran statistics. By and large, a regional convergence path with high conditional Ø-convergence, a lower dispersion of per capita incomes and a lesser mobility of countries along the ranking are shown to exist.
Keywords: O54; O47; R12; 330; Economic growth; regional convergence; spatial effects; Latin America